Structural Model Kekuatan Kualitas Website dalam Membangun Citra Perguruan Tinggi - Moch. Anang Karyawan; Mochamad Nurhadi; Ari Cahaya Puspitaningrum; Muhammad Septama Prasetya (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
The website is an information technology facility that is the main branding tool for universities. This research uses studies at tertiary institutions that have changed from high schools to universities. This change has an impact on reducing the number of users accessing the website, so it is necessary to analyze the quality of the website to improve the image of universities. The aim was to analyze the quality of the website on the image of the university by mediating brand awareness, and its impact on user satisfaction and the intention to revisit the university's website. This research is quantitative research with a survey method. The sampling technique used purposive sampling. Questionnaires were distributed to respondents who met the criteria via Google Form in 2023 and obtained 278 respondents. The analysis technique used was Partial Least Square with Structure Equation Modeling (PLS-SEM) using measurement model evaluation and structural model evaluation using the SmartPLS application. The results of this study indicate that there is a strong influence of website quality in building a college's brand image. Improving the quality of the website is proven to be able to increase brand awareness and the image of higher education institutions. The impact of improving the university's image is increasing website user satisfaction so that there is an intention from users to revisit the university's website in the future.